Halliday & Resnick principles of physics - Walker, Jearl (John Wiley & Sons, Inc., 2020)
Principles of Physics, now in its 11th edition, is renowned for teaching students, not just the basic concepts of physics, but also the superior problem-solving skills needed to apply what they have learned. With thematic modules and clear learning objectives, students will never be left asking, "Why am I learning this?" End-of-chapter questions range from the mathematically challenging to the conceptually complex, to truly instill in students a working knowledge of calculus-based physics. This new edition features problems that represent a "best of" selection reaching all the way back to the book's first publication. The strongest and most interesting questions from all the Principles of Physics editions will challenge and stimulate students as they learn how the world works. Altogether, this user-friendly text is peerless in its ability to help students build scientific literacy and physics skill.